Development, characterization, and cross-amplification of 17 microsatellite markers for Filipendula vulgaris - Čortan, Dijana; Krak, Karol; Vít, Petr; Mandák, Bohumil (Applications in plant sciences, 2019)
PREMISE: Polymorphic microsatellite markers were developed as a tool for genetic investigations of Filipendula vulgaris (Rosaceae) and related species. METHODS AND RESULTS: Seventeen new polymorphic microsatellite markers were developed for F. vulgaris using the Illumina MiSeq platform. Polymorphism of the 17 loci was tested in three populations. We identified a total of 203 alleles, ranging from four to 19 per locus, with levels of observed and expected heterozygosity ranging from 0.267 to 1.000 and 0.461 to 0.899, respectively. Primers were also tested for cross-amplification in three related species. Seven loci successfully cross-amplified in F. camtschatica and F. ulmaria, whereas we detected positive cross-amplification in only three loci in Geum urbanum. CONCLUSIONS: The newly developed microsatellite primers will serve as useful genetic tools for further population genetic studies on F. vulgaris and related species.
Keywords: Rosaceae; microsatellites; cross‐amplification; Filipendula vulgaris; perennial herb